Aggressiveness of Fusarium langsethiae isolates towards wheat, barley and oats in an in vitro leaf assay. - Opoku, Nelson; Back, Matthew; Edwards, Simon G. (Plant Breeding and Seed Science, 2011)
Fusarium langsethiae has been identified as the primary producer of HT-2 and T-2 in European cereals. HT-2 and T-2 are considered as two of the most potent trichothecenes mycotoxins and a public health concern in Europe. There is currently no legislation on HT-2 and T-2, however, there is a discussion limit of 500 µg kg -1 in unprocessed oats, 200 µg kg-1 for oat products and 50 µg kg-1 for infant food. There are limited data regarding F. langsethiae’s pathogenicity and mycotoxin production, but it is evident that its behaviour deviates from traditional trichothecene-producing Fusarium species. This experiment was aimed at assessing the aggressiveness (measured by lesion length) of 20 different F. langsethiae isolates on wheat, barley and oats using an in vitro detached leaf assay. There was a significant (P<0.001) difference between lesion lengths formed by different F. langsethiae isolates used. Isolate Fl/2004/17(a) caused the shortest lesion on all cereals and this was significantly (P<0.001) different from that caused by isolate Fl/0/08/009/1 which caused the longest lesion on all cereals used. A highly significant difference (P<0.001) was also observed between lesions on the different cereals (wheat, barley and oats). Lesions on oats were the longest, followed by barley with wheat showing the shortest lesions.